In-silico study of potential carboxylic acid derivatives as D-glutamate ligase inhibitors in Salmonella typhi - Muhammad I. Qadir; Hina Mushtaq; Tahira Mobeen (Kuwait Journal of Science)
Salmonella typhi is food-borne as well as water-borne pathogen, which is the main cause of typhoid fever. This disease is affecting people in both developing and underdeveloped countries. The emergence of multidrug resistance in S. typhi has encouraged researchers towards targeting novel pathways. UDP-N-acetylmuramoyl-L-alanine: D-glutamate ligase enzyme is involved in cell wall synthesis of the bacterium. Studies have shown that two carboxylic acids; acetic acid and lactic acid, have anti-bacterial activity. Present in-silico study investigated the potential of acetic acid derivative (2,4-Dihydroxybenzyliminodiacetic acid) and lactic acid derivative (ammonium lactate) to inhibit the peptidoglycan synthesis. These derivatives showed good potential as inhibitors of target protein. These compounds can have a pharmaceutical application in drug development against the disease.